Susceptibility to peroxidation and fatty acid composition of fresh boar semen obtained from different hog farms - Marmunti, Monica Edith (2012)
Objectives of this study were to determine the fatty acid composition and to analyze the sensitivity to lipid peroxidation of different boar fresh semen samples from two herds, H1 and H2. Lipid peroxidation was evaluated using chemiluminescence (cpm/mg of protein) and fatty acid profile by means of gas chromatography. The saturated fatty acid content found in the analyzed spermatozoa was approximately 43% in H1 and 33% in H2, whereas the total unsaturated fatty acid content was 47% in H1 and 59% in H2. When control and ascorbate-Fe++ dependent samples were compared, it was observed a significant increase in light emission. Consequently, significant decrease in the percentage of the polyunsaturated fatty acids was determined, being more affected: C22: 5 n6 and C22: 6 n3 in both herds, whereas C20: 4 n6 and C22: 4 n6 only in H2. The great amounts of polyunsaturated fatty acids found in H2 samples could be related to the loss of acrosomal integrity. Our results indicate that boar semen contains great amounts of polyunsaturated fatty acid in its composition, which were vulnerable to the lipid peroxidation.